Hubungan Body Dissatisfaction dan Perilaku Diet pada Mahasiswa Universitas Katolik Soegijapranata Semarang - Meiliana Meiliana; Vionna Valentina; Christiana Retnaningsih (Soegijapranata Catholic University, 2018)
Body dissatisfaction reflects negative body image which may promote behavior changes in order to improve appearance. This study investigates the association between body dissatisfaction and dietary behavior of young adults. College students (n=379) completed a survey on body dissatisfaction and dietary behavior in a cross-sectional research design and convenience non-probability sampling method. Information about nutritional status, reasons of dieting, dieting methods, dietary behavior scale, and body dissatisfaction scale were collected. Most respondents had normal weight status, poor dietary behavior, and body dissatisfaction. Obtaining attractive body shape was the most voted reason of dieting, while cutting eating frequency was the most frequent dieting method. There was a weak and contradicting (r=-0.095) association between body dissatisfaction and dietary behavior which meant that body dissatisfaction was followed by poor dietary behavior